The Role of Herman Willem Daendels in Politics in the Dutch East Indies 1808-1811 - Pratama, Yogi (Swarnadwipa, 2024)
This research aims to describe the role of Herman Willem Daendels in the Dutch East Indies while he was governor general in politics in 1808-1811. Starting from the bankruptcy of the VOC in the Dutch East Indies, the appointment of Daendels as leader in the Dutch Indies to the policies implemented by Daendles while leading, especially in the political field. The research method uses historical or historical methods in the form of descriptive narrative through 4 stages of heuristics, source criticism, interpretation, and historiography (historical writing). Based on research results, Herman Willem Daendels' role in the political field was to carry out significant administrative reforms. Daendels changed the previously decentralized administrative system to a more centralized one, establishing a new, more efficient bureaucracy by introducing salaries for regents as colonial government employees, trying to reduce the level of corruption that was rampant during the VOC government and increasing their loyalty and performance by providing appropriate compensation and abolishing feudal structures and overhauling power relations between the Dutch East Indies government and local rulers in Java. This research provides insight into the role of Herman Willem Daendels in the Dutch East Indies while he was governor general, especially in the political field in 1808-1811.